Pengembangan Model Examples Non Examples Dengan Make A Match Dalam Meningkatkan Hasil Belajar IPS Siswa Kelas IV SD Negeri 1 Karangrayung Grobogan Tahun Pelajaran 2015/2016 - Roby Mahendra, Galih; , Dr. Achmad Fathoni, S.E., M.Pd (2016)
This study aims to determine: (1) Is the mix between learning model Examples Non-Examples to Make a Match products in improving learning outcomes IPS fourth grade students of SD Negeri 1 Karangrayung Grobogan Academic Year 2015/2016, (2) Is the product resulting from a blend of learning model Examples Non-Examples to Make a Match can be effective after testing in the fourth grade students of SD Negeri 1 Karangrayung Grobogan Academic Year 2015/2016. This study is a research and development (Research and Development) with research subjects fourth grade students of SD Negeri 1 Karangrayung Grobogan. Data collection techniques using observation, testing, and documentation. Data analysis techniques in the form of descriptive statistics. The conclusion of this study are: (1) There is a learning model products produced by the combination of the learning model Examples Non-Examples to Make a Match in improving learning outcomes IPS fourth grade students of SD Negeri 1 Karangrayung Grobogan Academic Year 2015/2016. Development of Non-Examples Examples models to Make a Match produces the model Narrating Pictures. Narrating Model Pictures is a learning model blend of strategy Non Example Example using drawing as a medium with a strategy Make a Match using cards as the medium. The learning model Narrating Pictures is one of the innovations of the learning model used in the schools. Thus when the teacher provides materials to the student by using model Narrating Pictures, students are able to understand the material so well that its value can achieve mastery Minimum Criteria (KKM) and the complete study results. (2) The product resulting from the combination of the learning model Examples Non-Examples to Make a Match proven to be effective after testing in the fourth grade students of SD Negeri 1 Karangrayung Grobogan Academic Year 2015/2016. The effectiveness of these products can be seen in the results of social studies students has increased. Based on the model Narrating Pictures Randomaized Pretest try learning outcomes of students who reached the KKM (≥ 60) amounted to 21.92%, after testing phase I increased to 40.96%, and the phase II trial increased to 70.72%. Keywords: Learning Outcomes Social Sciences, Narrating Pictures, Examples Non-Examples, Make A Match